Case reportHLA-B27 (antigen) in retroperitoneal fibrosis in a family - Yazdani, Mohammad; Shadmehr, Afshin (Archives of Medical Science, 2007)
Idiopathic retroperitoneal fibrosis is a rare disease of undetermined aetiology. It is important to distinguish this entity from retroperitoneal fibrosis secondary to malignancy or specific inflammatory disease. There have been no prior means of excluding this condition without surgical exploration and histopathologic study of the excised tissue. A genetic predisposition is suggested for the development of idiopathic primary retroperitoneal fibrosis in patients who are HLA-B27 antigen positive. In this study we present three cases of idiopathic retroperitoneal fibrosis in a family (2 brothers and their grandfather). The presence of HLA-B27 antigen positivity was identified in two of them.